(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The involvement of Chinese women in politics remains low, as evidenced by the number of Chinese women in the State Legislative Assembly, the House of Representatives, and those holding positions in the cabinet, either as ministers or deputy ministers. Political literacy is one indicator influencing Chinese women’s political participation in Peninsular Malaysia. Our study examines the political literacy among Chinese female representatives in Peninsular Malaysia and its impact on their political participation. We successfully interviewed seven informants: Chinese female political representatives from the MCA, DAP, and PKR parties in Peninsular Malaysia. The interview results were recorded, transcribed, and thematically analyzed based on the frequency and similarity of the informants’ views. We found that political literacy among Chinese women is high, as they recognize the importance of women’s involvement in politics. However, the overall political participation of Chinese women in Malaysia remains low due to other indicators influencing their participation in addition to political literacy. We propose strategies to empower Chinese women in the political arena in Malaysia. We emphasize the need for more research on the involvement of Chinese women in politics to ensure they are not marginalized, as their voices are essential for representing and advocating for their needs and interests in Malaysia.